Morphology of silicon carbide synthesized using laser ablation of a mixture of nanofibrous carbon with xerogel - Kuvshinov, G. G.; Krutskii, Yu L.; Orishich, A. M.; Chukanov, I. S.; Varfolomeeva, A. S.; Afonin, Yu V.; Zaikovskii, V. I.; Kuvshinov, D. G. (Nanotechnologies in Russia, 2012)
The results of studying products obtained using the laser ablation of a composite consisting of granular nanofibrous carbon impregnated by an organic-silicon compound-tetraethoxysilane-based alcogel-are presented. A continuous CO 2 laser with a power of 0.6 kW was used as a radiation source; the radiation flux density was 3.4 W/cm 2, the pressure in the reactor was 770-780 torr, and helium was used as the medium. The material, which was evaporated and gathered from the condenser surface and also taken from the target at the point of laser-beam impact, was studied using high-resolution electron microscopy on an electron microscope JEM-2010 with the application of local energy-dispersive X-ray microanalysis on an EDAX spectrometer. It has been found that the evaporated and condensed material contains nanostructures-nanorods 20 nm in diameter formed by transverse silicon carbide layers and covered by a layer of silicon dioxide. Silicon carbide particles about 15 nm in size are also revealed in the target material after its exposure to the laser beam. © 2012 Pleiades Publishing, Ltd.
Keywords: Laser ablation; Silicon carbide; Silicon carbide particle; Radiation power density; High melting compound